Single Candidate: A Setback to Indonesian Democracy? - Muharam, Ricky Santoso; Pradhanawati, Ari; Fitriyah, Fitriyah; Supratiwi, Supratiwi (Technium Social Sciences Journal, 2023)
The increase in regional head candidates was held in 2015. There were 4 single candidates. In 2017, there were 9 single candidates; in 2018, there were 16 single candidate pairs; for the 2020 regional elections, there was an increase to 25. The phenomenon of single candidates in the Pilkada and the increasing trend of each provincial head election is increasingly attractive to be studied more deeply. This research uses a qualitative approach to analysis by emphasizing process and meaning. Various literature studies related to research on implementing single candidates in simultaneous regional elections from 2015, 2017, 2018, and 2020. Some of the factors of a single candidate for the regional head are the failure of political parties in the cadre process, the high cost of political dowries, the legitimacy of the law, and the difficulty of the requirements for independent candidates to run for regional head elections. The phenomenon of a single candidate in the democratic system in Indonesia certainly attracts the attention of academics, politicians, and the public to study and follow the development process of the local democratic system. The presence of independent candidates will provide an alternative solution to regions in regional head elections that do not have competitors offered by political parties.